FinTechs and digital financial services landscape of Malawi: A supply-side analysis - Frank Makoza (ZBW - Leibniz Information Centre for Economics, 2026)
Financial Technology (FinTech) organisations are perceived to be enablers of digital financial services in Malawi. They support efficient business transactions, secure payments instead of cash, lower transactions costs and support financial inclusion. While the phenomenon of FinTech has received attention among scholars, FinTech landscape of Malawi (e.g. supply-side) is not well documented. This paper analysed the FinTech landscape of Malawi focusing on profiling organisations, digital financial services and regulations. Using secondary data, the findings showed diversity of FinTech services e.g. mobile money, digital wallets, card-based payments, cloud banking services, microfinance and international remittance services. FinTechs operating in formal sector were regulated, while other FinTechs offering services for cryptocurrencies and crowdfunding platforms were not covered in the financial sector regulations. The study contributes towards literature on FinTechs in Malawi and highlights areas of further research.
Keywords: 330; Financial Technology; FinTechs; Supply-side; Digital financial services; Malawi